Differentiating bubble-free layers from melt layers in ice cores using noble gases. Issue 227 (2015) - Orsi, Anais J.; Kawamura, Kenji; Fegyveresi, John M.; Headly, Melissa A.; Alley, Richard B.; Severinghaus, Jeffrey P.
Abstract: Melt layers are clear indicators of extreme summer warmth on polar ice caps. The visual identification of refrozen meltwater as clear bubble-free layers cannot be used to study some past warm periods, because, in deeper ice, bubbles are lost to clathrate formation. We present here a reliable method to detect melt events, based on the analysis of Kr/Ar and Xe/Ar ratios in ice cores, and apply it to the detection of melt in clathrate ice from the Eemian at NEEM, Greenland. Additionally, melt layers in ice cores can compromise the integrity of the gas record by dissolving soluble gases, or by altering gas transport in the firn, which affects the gas chronology. We find that the easily visible 1 mm thick bubble-free layers in the WAIS Divide ice core do not contain sufficient melt to alter the gas composition in the core, and do not cause artifacts or discontinuities in the gas chronology. The presence of these layers during winter, and the absence of anomalies in soluble gases, suggests that these layers can be formed by processes other than refreezing of meltwater. Consequently, the absence of bubbles in thin crusts is not in itself proof of a melt event.